PENGARUH TAKARAN UREA TERHADAP HASIL DAN MUTU BENIH BAWANG MERAH - Sari Megawati; Rajiman; Ismadi; Abid Raif Rahmatullah (Jurnal Pertanian Agros, 2026)
Shallot (Allium ascalonicum L.) is a high-value horticultural commodity with continuously increasing demand. The success of shallot cultivation, particularly for seed production, largely depends on the availability of high-quality seeds, which is influenced by fertilization practices. Nitrogen (N) plays an important role in plant growth and yield formation; however, inappropriate N application can reduce seed quality. This study aimed to evaluate the effects of different urea fertilizer doses on the growth, yield, and seed quality of shallots, as well as to determine the optimal and efficient urea dosage. The research was conducted in Nglipar District, Gunungkidul Regency, Special Region of Yogyakarta, from April to December 2025, using a Randomized Complete Block Design with four urea dose treatments, namely 0, 100, 150, and 200 kg/ha, each replicated six times. Observed parameters included vegetative growth, yield components, and the physical and chemical quality of bulbs. The results showed that increasing urea doses tended to enhance plant height and leaf number up to a certain level, but did not always have a significant effect at the maximum vegetative stage. A urea dose of 100 kg/ha produced the highest bulb weight, productivity, and the best physical and chemical bulb quality compared to higher doses. Application of urea above the optimal rate reduced yield and nitrogen use efficiency. Therefore, a urea dose of 100 kg/ha is recommended as the optimal rate to improve the quantity and quality of shallot seed.